DEVELOPMENT AND PRECODIFICATION OF A LITHOSPHERE QUESTIONNAIRE AS A TOOL IN EDUCATIONAL RESEARCH (GEOSCIENCES) - Bakopoulou, A.; Antonarakou, A.; Lozios, S.; Zambetakis - Lekkas, A. (Bulletin of the Geological Society of Greece, 2016)
This paper presents the theoretical approach and the technical steps for the development of a questionnaire on lithosphere for the 1st class of Greek junior high school. It, also, discusses the importance and the multifunctional role of such a questionnaire (i.e. GCI tool). Furthermore it presents an innovative precodification of open-ended questions based on the set question - control question, which offers valid data for a qualitative study like this. The cognitional control table offers abundant data about students’ cognitional structure and about whether conceptual change has been achieved.